Land Use Dan Zonasi Kawasan Cagar Budaya Kotabaru Yogyakarta, Berdasarkan Konsep Garden City - Yunita Kesuma (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
The Kotabaru area (formerly called nieuwe wijk) which is an effort to expand the city creates a "new town in town". The zoning pattern of Garden City is a concentric radial model, where there are main principles, namely: a) Civic center (city park at the core of the area) in the form of open space in the middle of the area used as a green area and surrounded by public buildings; b) Crystal Palace (public facilities outside central park); The outer ring of the crystal palace is c) a group of houses overlooking the boulevard, d) The outer ring as a market, warehouse, factory, and other service facilities. This paper will focus on looking at the changes in landscape function that have occurred in the New City of Yogyakarta from several decades. Landscape changes in this case are changes in land use and zoning of Cultural Heritage areas, including: built land (settlements, shops, government building offices, public facilities, and others), open land (parks/fields), watery land (rivers, and canals), and green land (gardens and RTH). To obtain accurate data support, relevant documentation is carried out; land cover data, interpretation of historical maps/regional morphology, aerial photographs and collection of statistical data